Risk factors and prevention of breakage of powerPICC solo catheters: A report of 4 cases (4例PowerPICC SOLO导管体内破损相关因素分析及预防措施) - CHEN Jie (陈杰); SHEN Yanfen (沈艳芬); DONG Jing (董静); WANG Xinpeng (王新朋); ZHEN Yuanyuan (郑媛媛); WANG Xiaozheng (王晓峥) (中西医结合护理)
This paper reviewed the clinical date of 4 patients with breakage of powerPICC solo catheters. The risk factors of catheter breakage were analyzed in perspectives of catheter materials, veins selection for PICC insertion and other issues. Preventive measures were also provided for further clinical research and practice. (本文对4例末端瓣膜式耐高压注射型经外周静脉置入中心静脉导管(PowerPICC SOLO)导管体内破损病例进行总结, 从导管材质、置管静脉选择等视角剖析导管体内破损的相关因素并采取相应预防措施, 以期为临床研究及实践提供参考。)